2017
DOI: 10.1021/acs.jpcc.6b12168
|View full text |Cite
|
Sign up to set email alerts
|

Layer-by-Layer Assembled Film of Asphaltenes/Polyacrylamide and Its Stability of Water-in-Oil Emulsions: A Combined Experimental and Simulation Study

Abstract: Emulsions with interface-active components at the water/oil (w/o) interface are of fundamental and practical interest in many fields. Here we investigate the interfacial films of asphaltenes and asphaltenes/polyacrylamide (PAM) at the w/o interface of water-in-crude oil emulsions. With the combination of the dissipative particle dynamics simulation and experimental observation, the molecular interactions of asphaltenes and asphaltenes/PAM at the w/o interface are extensively analyzed. We show that the rigid me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
35
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 44 publications
(35 citation statements)
references
References 61 publications
0
35
0
Order By: Relevance
“…9,12 In our previous studies, it was found that the rigid mechanical lm of asphaltenes originates from (i) rigid structure of polycyclic aromatic hydrocarbons (PAHs) and (ii) the pp bonding interactions between the PAHs of asphaltenes. 13 Moreover, a layer-by-layer assembled architecture lm was formed at the W/O interface when the system in presence of polyacrylamide (PAM). This layer-by-layer assembled architecture lm exhibits great viscoelasticity and rheology properties which enhances the stability of water-in-oil emulsions.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…9,12 In our previous studies, it was found that the rigid mechanical lm of asphaltenes originates from (i) rigid structure of polycyclic aromatic hydrocarbons (PAHs) and (ii) the pp bonding interactions between the PAHs of asphaltenes. 13 Moreover, a layer-by-layer assembled architecture lm was formed at the W/O interface when the system in presence of polyacrylamide (PAM). This layer-by-layer assembled architecture lm exhibits great viscoelasticity and rheology properties which enhances the stability of water-in-oil emulsions.…”
Section: Introductionmentioning
confidence: 99%
“…Though a large number of the aforementioned studies have been reported, a further understanding of the nanoaggregate structure and emulsion stability of asphaltenes at the O/W interface is still needed, especially at mesoscopic scale. 13 In this work, we employed dissipative particle dynamics (DPD) simulations for studying the nanoaggregate structures of asphaltenes at water/toluene interface with the mesoscopic scale. 13,22 DPD simulations method are an excellent technology for the simulation of coarse-grained systems over considerable length and time scales up to the mesoscopic scale.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the values of these peaks increase with increase in the surface coverage of the polymers. According to the density profiles, the self‐assembled monolayer thickness can be calculated by the “90‐10” criterion, which is defined as the distance along the interface over the solvent densities distributed from 90% to 10% of their bulk value. The self‐assembled monolayer thickness of the end‐functionalized polymer at the vapor/liquid interface is 3.84σ, 4.74σ, 5.46σ when the surface coverage of polymer is φ = 3.02%, φ = 4.54%, and φ = 6.81%, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…The oil content decreased with increasing ratio of EO/PO at the same time. Indigenous components of crude oil such as asphaltenes, resins, naphthenic acids, and fine solids play important roles in stabilizing the oily wastewater, and the contents of EO in PEI99‐54 and PEI99‐11 were higher than the contents in the other corpolymers, which made PEI99‐54 and PEI99‐11 have stronger ability to remove the natural surfactants and the other indigenous components from the interface . Therefore, PEI99‐54 and PEI99‐11 showed a better performance in the treatment of oily wastewater.…”
Section: Resultsmentioning
confidence: 99%